AFTER THE STORM THE FLOOD COMES - Andréia Arruda de Oliveira Mosca; Vicente Rocha Silva (Sociedade & Natureza)
According to studies done by the World Resources Institute (a non –governmentalorganization based in Washington, DC) “ more than two thirds of the agricultural lands weredegraded due to erosion, pollution and impoverishment of the soils” It should be alerted thatthe challenge of the new millennium resides in the adequate use of the soil: only with itscorrect utilization the feeding attendance of the future generations will be guaranteed – atendency which was pointed out by U.N. since 1949. In reply to that question several recoveryinitiatives of degraded areas have been implemented and discussed in many countries. Thiswork points out some guidelines towards thematic approached in Brazil planning aiming atsustainability. It is mentioned, as follow, some Brazilian initiatives in order to argue andimplement the recovery of degraded areas.